Concerning selective neck dissections in oral squamous cell carcinoma - Yu V Alymov (Современная онкология, 2016)
Background. Incidence of oral cancer in Russia is 4.52 and mortality - 2.44. Head and neck cancer is characterized by the high risk of development of metastases in regional lymph nodes (LN). LN status exerts influence on the treatment plan and appears to be the major predictive factor. Regional metastases result into two-fold decrease of five-year survival. Treatment of metastatic LN is of prime importance.Objective. The aim of this manuscript was to illustrate and summarize publications devoted to selective neck dissections in patients with squamous cell carcinoma of the oral cavity (OC).Results. Classic radical neck dissection is the gold standard of surgical treatment of OC cancer, characterized by regional metastases. However, metastases in neck LN of the IV- and V-th level are rarely present in patients with oral cancer. Therefore, efficiency of less extensive neck surgery is of great interest of up-to-date investigations. It was established, that selective neck dissection increases disease-free survival among patients with cT1-4N0M0 oral cancer in comparison with watchful waiting. Comparison of preventive selective neck dissections with preventive and curative modified neck dissections also indicates, that these methods of surgical treatment have equal efficacy.Conclusion. Selective neck dissection is feasible treatment method of сT1-4N0M0 oral cancer. Nevertheless, comparison studies of preventive selective and modified neck dissections, were characterized by disparate design and high probability of systematic errors. Moreover, another aspect, that must be solved, is the number of LN levels to be dissected during selective neck dissection. Thus, conception of selective neck dissection in patients with clinically negative LN is changing and requires further investigation.